Love and Loss As Seen in Celine Dion’s Song Lyrics: Psychologycal Analysis - Helmita Helmita; Yelfina Gaho Yelfina Gaho (Fakultas Sastra Universitas Ekasakti, 2026)
This research is motivated by the personality of the songwriter performed by Celine Dion. The purpose of this research is to analyze the personality of the songwriter, the forms of loss experienced by the songwriter, and the strength of love experienced by the songwriter in the songs performed by Celine Dion. The method used in this research is descriptive qualitative. The data in this song are quotes, sentences related to personality, forms of loss, and the strength of love experienced by the songwriter which are reflected in the songs performed by Celine Dion. The data collection technique in this research is reading, marking data, recording and distinguishing the collected data based on the personality, forms of loss, and the strength of love of the songwriter which are reflected in the songs performed by Celine Dion. The results of this research indicate that in the songs performed by Celine Dion the form of the songswiriter personality consists of Id, Ego, and Super Ego, this is caused by feelings of love for someone, the form of loss experienced is losing oneself and losing love, and the strength of love felt is the strength of love for a partner or loved one and also the strength of self-love.